The national integration trajectory towards national development: the inculcation dynamics of english language nationhood values education in selected Malaysian secondary schools - Suranthiran Naidu, M. N. Naidu (2017)
The ethnically ‘compartmentalised’ Malaysian society characterised increasingly today by a state of constant ‘stable tension’ in the nation’s social fabric, can be attributed to the ‘divided’ education system. This is said to have resulted today in a lack of mutual understanding, particularly amongst the nation’s growing youth. The cardinal issue here is a knowledge deficiency amongst school-youth of positive cognitive learning towards developing a deep sense of a nationalistic ethos based on the national ideology, the Rukun Negara. As such, the primary objectives of this study are to firstly, look into the extent the English Language public school education curriculum can instill nationhood values in students, and secondly, how it can contribute towards the building of strong ‘social bridges’ amongst Malaysian school-youth. Thus, accordingly, this study uses both the qualitative and quantitative research approaches. Further, to investigate the problem statement of this study, the research methodology encompassed the study and analysis of materials from primary and secondary sources, such as journal articles, books, book chapters, official government statements, including internet-based materials. Interviews were conducted, with the respondents who consisted of groups of students, teachers, academics, and certain identified public individuals. A structured questionnaire survey was used to obtain information from the form two lower secondary and form four upper secondary students in public secondary schools. The findings of this study indicated that the form two students were more positively inclined towards the acceptance of nationhood values, than form four students; both student groups felt that the ‘education’ of English Language nationhood values can further enhance the said values in students. Further, they suggested that all education authorities need to do more to achieve the goal of national integration. The respondents opined emphatically that the learning of English can be a constructive platform for the nurturing of nationhood values in students. Nearly all the respondents strongly emphasised that the teacher is one of the nation’s key nation-builders, and is a crucial agent in ‘educating’ school-youth with nationhood values-based 'education', and further, the young Malaysian generation.